7c + 3d= -16 .. (1)
7c + 5d = -8 ... (2)
(2) - (1) 2d = 8
d = 4
By substitution
c = -4
2006-11-05 11:09:23
·
answer #1
·
answered by Wal C 6
·
0⤊
0⤋
write the equations as 7c+3D= -16 7c+5d= -8 Subtract the words from good to bottom. 7c minus 7c is 0. 3D-5d is -2d -16--8 is -8. You get -2d=-8. Divide -2 on both part to get d=4. Now to procure d. Plug d into between the equations. shall we are saying 7c+3(4)=-16. You get 7c+12=-16. Subtract 12 from both part. You get 7c=-28. Divide 7 from both part. You get c=-4. So your solutions are d=4 and c=-4. desire this helped good luck
2016-11-28 19:48:49
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
(1) 7c + 3d= -16
(2) 7c + 5d = -8 subtract (1) from (2)
2d=8
d=4
substitute in (2)
7c+5*4=-8
7c+20=-8
7c=-28
c=-4
check 7(-4)+3*4=-16
-28+12=-16
-16=-16
2006-11-05 11:07:35
·
answer #3
·
answered by yupchagee 7
·
0⤊
0⤋
7c+3d=-16
7c+5d=-8
--------------
deduct first from the second equation by changing + to - and wiseversa, -7c-3d=+16 deduct from second equetion:
-7c-3d=+16
7c+5d=-8
-------------
2d=8 d=4 put this in first equetion 7c+3*4=-16 or
7c+12= -16 or 7c= -16-12 0r 7c= -28
c=-28/7 c= -4
2006-11-05 11:24:25
·
answer #4
·
answered by sam n 1
·
0⤊
0⤋
7c+3d=-16
7c+3d(-3d)=-16(-3d) minus 3d from each side
7c=-16-3d
substitute -16-3d for 7c
-16-3d+5d= -8 add 16 to each side
-3d+5d=8
2d=8 divide each side by2
d=4
use first equation
7c+3(4)=-16
7c +12=-16
now subtract 12 from each side
7c=-28
divide by 7
c=-4
2006-11-05 11:19:29
·
answer #5
·
answered by JJ L 1
·
0⤊
0⤋
7c+3d=-16 ---- (i)
7c+5d=-8 ---- (ii)
Subtract (ii) from (i):
-2d = -8
d = 4
Substitute the value of d in (i):
7c + 3*4 = -16
7c = -16 - 12
7c = -28
c = -4
Therefore c = -4 and d = 4.
QED
2006-11-05 11:07:27
·
answer #6
·
answered by Fahd Shariff 3
·
0⤊
0⤋
7c + 3d = -16
7c + 5d = -8
Multiply top by -1
-7c - 3d = 16
7c + 5d = -8
2d = 8
d = 4
7c + 3(4) = -16
7c + 12 = -16
7c = -28
c = -4
ANS :
c = -4
d = 4
2006-11-05 12:37:24
·
answer #7
·
answered by Sherman81 6
·
0⤊
0⤋